Astrometry and photometry of asteroids from the UkrVO database of astroplates. Issue Volume 15:Issue S364(2019) (October 2021) - Vavilova, I.B.; Shatokhina, S.V.; Pakuliak, L.K.; Yizhakevych, O.M.; Eglitis, I.; Andruk, V.M.; Protsyuk, Yu.I.
Abstract: We present the developed methods of digitization, image processing, reduction, and scientific data mining with the latest reference catalogs, which allowed us to obtain a good positional and photometric accuracy in B-band of 6, 500 asteroids down to 17.5 m from the Ukrainian Virtual Observatory database of astroplates. The archive includes FON-Kyiv, FON-Kitab, FON-Dushanbe sky surveys (1981–1996) and astroplates of the Baldone and Tautenburg observatories. For some of asteroids, observations are either completely absent or not enough over the certain time interval to the moments of their official discoveries (about 300 such objects were found). Positional observations during these time scales are highly useful for a more detailed study of the dynamics and orbital parameters of asteroids as well as the obtained photometric parameters are very complementary with present-day data for studying changes in brightness and light curves.